Audit market concentration and audit quality - KALLAPUR, Sanjay (Institutional Knowledge at Singapore Management University, 2010)
Policymakers and regulators have been concerned about the impact of audit market concentration resulting from decline in the number of audit firms due to mergers and the demise of Arthur Andersen. In this paper we find a positive association between audit market concentration (Herfindahl index) at the MSA level and audit quality (measured by discretionary accruals and the Dechow-Dichev (2002) measure of accrual quality). We control for fixed year effects, therefore our results are unlikely to be affected by the increase in concentration due to Andersen’s demise contemporaneous with an increase in audit quality because of regulatory measures such as SOX. Our results are robust to alternative concentration and audit quality measures, and several sensitivity tests attempting to rule out omitted variables correlated with client firms’ MSA location or attributes of clients and auditors. Our results are also robust to controls for endogeneity between audit market concentration and audit quality. Our evidence therefore supports the Government Accountability Office (2003, 2008) conclusions that increased audit market concentration is not currently a cause for concern.